Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
2x - 3y = - 2 → (1)
4x + y = 24 → (2)
Multiplying (1) by - 2 and adding to (2) gives
- 4x + 6y = 4 → (3)
Add (2) and (3) term by term
(4x - 4x) + (y + 6y) = (24 + 4), that is
7y = 28 ( divide both sides by 7 )
y = 4
Substitute y = 4 into either of the 2 equations
Substituting y = 4 into (2)
4x + 4 = 24 ( subtract 4 from both sides )
4x = 20 ( divide both sides by 4 )
x = 5
Thus the answers x = 5 and y = 4 are the same as her first method
Answer: 3.3%
Step-by-step explanation:
Amount = prt / 100
3075.21 = (2152 x r x 13)/100
Answer:
-4x+y=7
Step-by-step explanation:
lets say you have y=4x+7 (linear equation)
to conver it to standard form you've got to make it Ax+By=C
so you minus the 4x and you should have -4x+y=7 for your standard form
Answer:
g(4)=f(2)
Step-by-step explanation:
f(2)=3(2)-1
f(2)=6-1
f(2)=5
We then get:
g(x)=f(2)
subsitute 5 for f(2)
g(x)=5
now solve
5=2x-3
add 3
8=2x
divide 2
4=x
so the answer is x=4 or
g(4)=f(2)
Answer:4/3x²+8x−20
Step-by-step explanation:Combine Like Terms:
=x+
4
3
x2+7x+−20
=(
4
3
x2)+(x+7x)+(−20)
=
4
3
x2+8x+−20